Analysis of ACI Godrej Agrovet Private Limited's accounts payable process and optimization strategies - Rifat, Sabbir Ahmed (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.